Bleeding efficiency, microbiological quality and oxidative stability of meat from goats subjected to slaughter without stunning in comparison with different methods of pre-slaughter electrical stunning - Sabow, Azad Behnan; Idrus, Zulkifli; Goh, Yong Meng; Ab Kadir, Mohd Zainal Abidin; Kaka, Ubedullah; Imlan, Jurhamid Columbres; Abubakar, Ahmed Abubakar; Adeyemi, Kazeem Dauda; Sazili, Awis Qurni (Public Library of Science, 2016)
The influence of pre-slaughter electrical stunning techniques and slaughter without stunning on bleeding efficiency and shelf life of chevon during a 14 d postmortem aging were assessed. Thirty two Boer crossbred bucks were randomly assigned to four slaughtering techniques viz slaughter without stunning (SWS), low frequency head-only electrical stunning (LFHO; 1 A for 3 s at a frequency of 50 Hz), low frequency head-to-back electrical stunning (LFHB; 1 A for 3 s at a frequency of 50 Hz) and high frequency head-to-back electrical stunning (HFHB; 1 A for 3 s at a frequency of 850 Hz). The SWS, LFHO and HFHB goats had higher (p<0.05) blood loss and lower residual hemoglobin in muscle compared to LFHB. The LFHB meat had higher (p<0.05) TBARS value than other treatments on d 7 and 14 d postmortem. Slaughtering methods had no effect on protein oxidation. Higher bacterial counts were observed in LFHB meat compared to those from SWS, LFHO and HFHB after 3 d postmortem. Results indicate that the low bleed-out in LFHB lowered the lipid oxidative stability and microbiological quality of chevon during aging.